Are the Positions in the Word Ranking of Competitive Alpine Skiers Explainable by Prominent Polymorphisms in Regulatory Genes of Mechanical and Metabolic Muscle Functioning? - Gasser, Benedikt; Frey, Walter O.; Valdivieso, Paola; Scherr, Johannes; Kopf, Juana; Spörri, Jörg; Flück, Martin (Research quarterly for exercise and sport, 2025)
Background: The success of competitive alpine skiers with respective to their world ranking (WR) positions might be associated with prominent gene polymorphisms. Methods: Twenty-six competitive alpine skiers were followed from 2015 to 2019 for their WR positions (FIS-ranking). Using PCR, the genotypes of ACE-I/D, TNC, ACTN3, and PTK2 were identified. The correlations between the discipline-specific WR position (slalom-SL, giant slalom-GS, super G-SG, downhill-DH, and alpine combined-AC) and gene polymorphisms were analyzed concerning an influence with multivariate regression models. Results: The WR position and the ACE gene as well as the copy number of the ACE I-allele exhibited reciprocal relationships for speed specialists (SG and DH) but not for technical specialists (SL and GS). Similarly, the gene polymorphisms ACTN3 and (partly) PTK2 were associated with the WR position in disciplines characterized by a high number of turns (technical specialists-SL and GS) and speed (speed-specialists-SG and DH), respectively. Conclusions: Our findings emphasize the contributions of aerobic and cardiovascular metabolism in fueling muscle work and recovering from muscle fatigue for competitive success in slalom-driven skiing disciplines and highlight the contributions of sequence variants in the genes ACE, TNC, and ACTN3.